Pelatihan Pemanfaatan Aplikasi LinkedIn dan Jobstreet sebagai Peluang Kerja Kepada Siswa SMKN 41 Jakarta - Aulia Zahrannissa Yunash; Kaila Aura Mevalia; Hanisyah Claudya Hermanto; Aniek Irawatie; Lilik Zulaihah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
This article discusses LinkedIn and Jobstreet training for Vocational High School students as a form of readiness for them before taking higher education or as a guide for them to get a job and also a form of their experience in terms of self branding. LinkedIn and JObstreet applications have many benefits that can bring us closer to the world of work, such as finding job vacancies, looking for internship opportunities at the desired company and as a provision to train and develop previously owned skills. Through this Community Service activity, students will be taught how to make a CV properly and correctly and then the results of making CV will be promoted through LinkedIn and Jobstreet applications. The method we use is the training method. Training itself can’t be separated from skill development, clear goal measurement, and attitude changes which are then applied with several choices of methods according to the needs of the environment. The training method we use in this Community Service is direct training based on R-Learning or learning conducted through electronic intermediaries such as with the help of electronic intermediaries such as laptops. The Community Service Activities that we carry out have the aim of being a form of real action towards the golden Indonesia 2045 later. By instilling good leadership values and always having a strong sense of love for the country and developing a sense of state defense to maintain a good and wise generation.